Motion verbs related to Javanese traditional fishing activities: a natural semantic metalanguage approach - Agus Subiyanto; Nurhayati Nurhayati; M. Suryadi; Peter Suwarno (Cogent Arts & Humanities)
Javanese fishermen use motion verbs, some of which are semantically very complex as a single lexical item can encode more than four semantic components. Compared to motion verbs across languages, which commonly contain two semantic components, the motion verbs used by the fishermen are more complex, and this raises the question of how to disentangle the components to accurately describe the verbs. This article aims to discuss the motion verbs used by the fishermen and how these verbs are decomposed into their semantic elements. The theory used in this study is the natural semantic metalanguage (NSM), a theory of semantics pioneered by Anna Wierzbicka. This study used data from fishermen living in Semarang, Demak and Kendal, representing areas of Central Java, Indonesia. The data were collected through observation and interview methods and analyzed using the NSM model of explication. The result shows that motion verbs used by the fishermen can be classified into the verbs expressing ‘going to the sea’, ‘coming back home from the sea’ and ‘motion activities on the sea’. Some of the verbs contain five to seven semantic elements, covering MOTION, FIGURE, PATH, GROUND, MANNER, MEDIUM and GOAL.